2014
DOI: 10.1051/0004-6361/201423616
|View full text |Cite
|
Sign up to set email alerts
|

The insignificant evolution of the richness-mass relation of galaxy clusters

Abstract: We analysed the richness-mass scaling of 23 very massive clusters at 0.15 < z < 0.55 with homogenously measured weak-lensing masses and richnesses within a fixed aperture of 0.5 Mpc radius. We found that the richness-mass scaling is very tight (the scatter is <0.09 dex with 90% probability) and independent of cluster evolutionary status and morphology. This implies a close association between infall and evolution of dark matter and galaxies in the central region of clusters. We also found that the evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 49 publications
11
37
2
Order By: Relevance
“…They found that richness scales almost linearly with the projected weak-lensing mass (β Y |X = 1.3 ± 0.3), with a statistically insignificant evolution (γz = −0.7 ± 0.7). The evolution with mass measured in Andreon & Congdon (2014) is steeper than a previous result by Andreon & Bergé (2012), which used spherical masses and projected richnesses to find β Y |X = 0.46 ± 0.12.…”
Section: λ-M∆contrasting
confidence: 70%
See 1 more Smart Citation
“…They found that richness scales almost linearly with the projected weak-lensing mass (β Y |X = 1.3 ± 0.3), with a statistically insignificant evolution (γz = −0.7 ± 0.7). The evolution with mass measured in Andreon & Congdon (2014) is steeper than a previous result by Andreon & Bergé (2012), which used spherical masses and projected richnesses to find β Y |X = 0.46 ± 0.12.…”
Section: λ-M∆contrasting
confidence: 70%
“…Wen, Han & Liu (2009) considered a compilation of clusters whose masses had been estimated by X-ray or weak-lensing methods to infer a slope of βY -Z = 1.17 ± 0.03. Andreon & Congdon (2014) studied the mass-richness scaling for a sub-sample of the CCCP clusters (The Canadian Cluster Comparison Project, Hoekstra et al 2012). They found that richness scales almost linearly with the projected weak-lensing mass (β Y |X = 1.3 ± 0.3), with a statistically insignificant evolution (γz = −0.7 ± 0.7).…”
Section: λ-M∆mentioning
confidence: 99%
“…Note that the results of this fit have been used to obtain the completeness and purity curves for different observable M * CL in §5.2. The M * CL |M h relation appears not to evolve with redshift, in agreement with other works (Lin et al 2006;Andreon & Congdon 2014;Saro et al 2015). In Fig.…”
Section: Observable-dark Matter Halo Mass Relationsupporting
confidence: 92%
“…Lin et al 2006;Andreon 2010;Andreon & Congdon 2014;Saro et al 2015), we have model the M * CL |M h relation with a log-log relation as follows:…”
Section: Observable-dark Matter Halo Mass Relationmentioning
confidence: 99%
“…However, we would expect the richness and luminosity mass proxies to be strongly dependent on the evolution of the galaxy LF within galaxy groups and clusters. Recent work implies that there may be little evolution in the mass-richness proxy (Andreon & Congdon 2014), though as this work uses a specific subset of galaxies to define richness, the result cannot necessarily be extrapolated to our richness proxy.…”
Section: Uncorrected Effectsmentioning
confidence: 98%